Larval morphology of the water mite Forelia brevipes (Neuman, 1880) (Acari: Hydrachnidia: Pionidae) - Tuzovskij, Petr V. (Zootaxa, 2019)
The fauna of the genus Forelia collected in Russia currently includes six species: F. brevipes, F. diaphana (Croneberg, 1899), F. liliacea (Müller, 1776), F. mutata (Piersig, 1901), F. samarica Tuzovskij, 1997 and F. variegator (Koch, 1837) (Uchida 1936, Sokolow 1940, Tuzovskij 1997). The larvae are known in F. liliacea, F. variegator (Wainstein 1980) and F. samarica (Tuzovskij 1997). Larvae of the genus Forelia are abdominal parasites of chironomid Diptera (Kouwets & Davids 1984, Smit & Oliver 1986). The aim of this paper is to present the morphology of the previously unknown larva of F. brevipes and to give an identification key for larvae of the genus Forelia species known in Russia.